Analisis Penerapan Akad Al-Ju’alah pada Perusahaan Multi Level Marketing: Studi atas Perusahaan HNI-HPAI - Rani Febriyanni; Marliyah Marliyah; Tuti Anggraini (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This research is to find out whether the bonus given by PT. HNI-HPAI is in accordance with the ju'alah contract. The method in this study is a descriptive analysis method from personal studies on various information such as websites, desktop sites, and other social media. The research shows that PT HPAI adheres to a Multilevel Marketing business work system based on Islamic sharia. There is an element of service in the MLM system, meaning that a distributor sells goods that do not belong to him and he gets a wage from a percentage of the price of the goods and if he can sell according to the target he gets a bonus or gift set by the company. Bonuses or gifts in Islam are called al-jualah. Sell ​​is a wage or gift that has been promised to someone because he has done a job and the wage/gift can be given because the work that has been determined has been completed. According to the DSN fatwa NUMBER 62/DSNMUI/XII/2007 regarding the al-jualah contract, there are 5 conditions that must be considered by multi-level marketing companies, especially sharia-based MLM. PT. HNI-HPAI as a company that adheres to the MLM work system has met the requirements of the DSN fatwa. Keywords: MLM, ju'âlah, HNI-HPAI